2022
DOI: 10.26803/ijlter.21.8.16
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Professional Training on In-service Secondary School Physics 'Teachers' Motivation to Use Problem-Based Learning

Abstract: Professional training for in-service teachers is at an utmost level to improve their teaching practices. Therefore, this study aimed to assess the effect of professional training on in-service secondary school physics teachers' motivation to use Problem-Based Learning (PBL). A pre-and posttest quasi-experimental design was used to conduct the study. A two-day professional training on PBL was delivered as an independent variable, while teachers' motivation to use PBL was conceived as the dependent variable. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In this study, such outcomes from the attitude toward learning physics were effective (Bergin et al, 2018;Kampen et al, 2004;Kanyesigye et al, 2022b;Maryuningsih et al, 2019;Sahin, 2009;Selçuk & Çalis ¸kan, 2010). For instance, results from the study that investigated the effect of PBL on students' attitudes indicated that the experimental group was more satisfied than the control group (Selçuk & Çalis ¸kan, 2010).…”
Section: Pbl Increases Attitude Toward Physics and Physics Learningmentioning
confidence: 69%
See 1 more Smart Citation
“…In this study, such outcomes from the attitude toward learning physics were effective (Bergin et al, 2018;Kampen et al, 2004;Kanyesigye et al, 2022b;Maryuningsih et al, 2019;Sahin, 2009;Selçuk & Çalis ¸kan, 2010). For instance, results from the study that investigated the effect of PBL on students' attitudes indicated that the experimental group was more satisfied than the control group (Selçuk & Çalis ¸kan, 2010).…”
Section: Pbl Increases Attitude Toward Physics and Physics Learningmentioning
confidence: 69%
“…However, group work emphasizes interdependency, individual accountability, and the development of social skills that have been found to promote critical thinking and problem-solving skills. Also, it is argued that teachers need to be supported with continuous professional development to be well-equipped with new teaching and learning methods like PBL (Kanyesigye et al, 2022b). The success of implementation relies on the teachers to use PBL.…”
Section: Introductionmentioning
confidence: 99%
“…Many schools and universities are now utilizing digital technology and multimedia to aid in visualizing difficul and abstract physics concepts (Rahim et al, 2022;Sunaryo et al, 2022). Furthermore, many physics teachers are adopting project-based approaches (Yanti et al, 2019;Widyaningsih & Yusuf, 2019;Santyasa et al, 2020;Makkonen et al, 2021) and problem-based approaches (Fauzana, et al, 2019;Pane et al, 2021;Kanyesigye et al, 2022a;Kanyesigye, et al, 2022b;Fonseca et al, 2022) to motivate students and help them better understand physics concepts.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the study revealed the importance of professional training programs in developing student teachers' abilities to practice decision-making skills as well as motivating them to learn. Kanyesigye et al [36] assessed the influence of professional development on physics teachers' motivation to use active learning strategies such as problem-based learning (PBL). The findings showed that professional development greatly affected the motivation of physics teachers to employ the active learning approach in learning environments.…”
Section: -Introductionmentioning
confidence: 99%